Aquatic risk assessment of pesticides in Latin America. (October 2014) - Carriquiriborde, Pedro; Mirabella, Paula; Waichman, Andrea; Solomon, Keith; Van den Brink, Paul J; Maund, Steve
ABSTRACT Latin America is anticipated to be a major growth market for agriculture and production is increasing with use of technologies such as pesticides. Reports of contamination of aquatic ecosystems by pesticides in Latin America have raised concerns about potential for adverse ecological effects. In the registration process of pesticides, all countries require significant data packages on aquatic toxicology and environmental fate. However, there are usually no specific requirements to conduct an aquatic risk assessment. To address this issue, the Society of Environmental Toxicology and Chemistry organized a workshop that brought together scientists from academia, government, and industry to review and elaborate on aquatic risk assessment frameworks that can be implemented into regulation of pesticides in Latin America. The workshop concluded that the international framework for risk assessments (protection goals, effects, and exposure assessments, risk characterization, and risk mitigation) is broadly applicable in Latin America but needs further refinement for the use in the region. Some of the challenges associated with these refinements are discussed in the article. It was recognized that there is potential for data sharing both within and outside of the region where conditions are similar. However, there is a need for research to compare local species and environmental conditions to those in other jurisdictions to be able to evaluate the applicability of data used in other countries. Development should also focus on human resources as there is a need to build local capacity and capability, and scientific collaboration and exchange between stakeholders in industry, government, and academia is also important. The meeting also emphasized that, although establishing a regionally relevant risk assessment framework is important, this also needs to be accompanied by enforcement of developed regulations and good management practices to help protect aquatic habitats. Education, training, and communication efforts are needed to achieve this. Integr Environ Assess Manag 2014;10:539–542. © 2014 SETAC